Dose-Dependent Effects of Dietary Sargassum Extract on Growth and Feed Utilization of Juvenile Koi Carp - Amanda Ratu Valisha; Abdul Syukur; Nunik Cokroawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Koi (Cyprinus carpio) are a freshwater ornamental fish with high economic value, thus requiring feed that can support growth and efficient nutrient utilization. The purpose of this study was to examine how adding seaweed extract from Sargassum sp. to food affected the growth and survival of koi. Using a completely randomized design (CRD) with four treatments and three duplicates, the trial was carried out over a 30-day period. P0 (no Sargassum sp. extract applied), P1 (50 mL/kg of feed), P2 (100 mL/kg of feed), and P3 (150 mL/kg of feed) were the treatments. Survival rate, absolute length growth, absolute weight gain, feed conversion ratio (FCR), feed use efficiency (EPP), feed proximate composition, and water quality were among the factors noted. ANOVA at a 95% confidence level was used to evaluate the data, and where significant differences were discovered, Duncan's test was used. The findings demonstrated that while the addition of Sargassum sp. extract had no influence on survival rate, it had a substantial impact on absolute length growth, absolute weight growth, FCR, and EPP (P < 0.05). The greatest absolute weight increase of 62.00 g, the greatest absolute length growth of 15.17 cm, the lowest FCR of 1.09, and the highest EPP of 90.75% were all achieved by treatment P3. Nevertheless, additional testing revealed no discernible differences between P2 and P3. In every treatment group, the fish's survival rate was 100%. Therefore, the development and feed consumption efficiency of koi fish were ideally enhanced by the addition of Sargassum sp. extract at a concentration of 100 mL/kg of feed.